2009
DOI: 10.1007/s11307-009-0225-0
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Correlates of Differential Expression of Indoleamine 2,3-Dioxygenase in Human Brain Tumors

Abstract: Background-Tryptophan catabolism via the kynurenine pathway, mediated by indoleamine 2,3-dioxygenase (IDO), is a mechanism involved in tumor immuno-resistance. Positron emission tomography (PET) with α-[ 11 C]methyl-L-tryptophan (AMT) can quantify transport and metabolism of tryptophan in infiltrating gliomas and glio-neuronal tumors. In the present study, we investigated whether increased tryptophan metabolism in brain tumors measured by PET is related to expression of IDO in resected brain tumor specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 37 publications
(50 reference statements)
2
70
0
Order By: Relevance
“…15 Studies on brain tissue obtained at resective surgery from patients without autism but with tuberous sclerosis complex and intractable epilepsy or from patients with brain tumors who had undergone AMT PET scanning revealed that increased AMT uptake may represent tryptophan metabolism by the kynurenine pathway (which is related to brain inflammation) rather than the pathway for serotonin synthesis. 57,59 In the current study, semiquantitative analyses support our visual assessment that the asymmetries in basal ganglia and thalamus represent increased tryptophan metabolism, because the mean SUV from cases with no asymmetry had values that were closer to values of the lower side in cases who did show asymmetry. This observation is intriguing in light of accumulating evidence for a role of brain inflammation in ASD, as has been reported in both imaging and neuropathology studies.…”
Section: Discussionsupporting
confidence: 77%
“…15 Studies on brain tissue obtained at resective surgery from patients without autism but with tuberous sclerosis complex and intractable epilepsy or from patients with brain tumors who had undergone AMT PET scanning revealed that increased AMT uptake may represent tryptophan metabolism by the kynurenine pathway (which is related to brain inflammation) rather than the pathway for serotonin synthesis. 57,59 In the current study, semiquantitative analyses support our visual assessment that the asymmetries in basal ganglia and thalamus represent increased tryptophan metabolism, because the mean SUV from cases with no asymmetry had values that were closer to values of the lower side in cases who did show asymmetry. This observation is intriguing in light of accumulating evidence for a role of brain inflammation in ASD, as has been reported in both imaging and neuropathology studies.…”
Section: Discussionsupporting
confidence: 77%
“…IDO is expressed at high levels in some solid tumors, including colorectal cancer, where it is thought to play a role in immune evasion (9,(29)(30)(31)(32). Consistent with this, the competitive IDO inhibitor 1-mT is currently in clinical trials for the treatment of relapsed or refractory solid tumors (13,33).…”
Section: Discussionmentioning
confidence: 79%
“…Preoperative AMT-PET studies were performed in 10 patients with meningioma (6 grade I, 2 grade II and 1 grade III) using a Siemens EXACT/ HR whole-body positron emission tomograph (Siemens Medical Systems) as described previously. 7,23 Briefly, after 6 h of fasting, AMT (37 MBq/kg) was administered intravenously. Twentyfive minutes after tracer injection, a dynamic emission scan of anti-mouse HRP (Southern Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…6 We have previously demonstrated tryptophan metabolism in a variety of human brain tumors using α-[ 11 C]methyl-l-trypto phan (AMT) positron emission tomography (PET) imaging. [7][8][9][10] AMT is an amino acid radiotracer, which can measure expression and activity of indoleamine 2,3-dioxygenase (IDO), the first and rate-limiting step of the kynurenine pathway of tryptophan catabolism, can enable tumor cells to effectively evade the host's immune response. The potential role of this system was investigated in meningiomas.…”
Section: Introductionmentioning
confidence: 99%